2023
DOI: 10.1039/d2sm01443b
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic synthesis of multilayered lipid–polymer hybrid nanoparticles for the formulation of low solubility drugs

Abstract: Hybrid phospholipid/block copolymer membranes where polymers and lipids are molecularly mixed or phase-separated into polymer-rich and lipid-rich domains are promising drug delivery materials. Harnessing the chemical diversity of polymers and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…Lipid–BCP hybrid membranes have synergistic structural and functional properties otherwise not achievable with the assembly of single components. Previous studies reported advanced properties of the lipid–polymer co-assemblies, e.g., improved mechanical stability, controllable solubility of encapsulated solutes in membranes, synergistic permeability of cargo drugs, and control of polymer crystallization and thermal properties. , Research on lipid–BCP hybrid membranes has been mainly conducted on lamellar systems in the form of vesicles dispersed in water, , monolayer suspended in water, or bilayers on solid supports, leaving a gap in our understanding of polymorphism of the lipid–BCP hybrid system. Nonetheless, lipid–BCP mixtures hold a huge potential in creating nonlamellar structures with increasingly complex structures and topologies given that each amphiphile has the ability to self-assemble into various nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid–BCP hybrid membranes have synergistic structural and functional properties otherwise not achievable with the assembly of single components. Previous studies reported advanced properties of the lipid–polymer co-assemblies, e.g., improved mechanical stability, controllable solubility of encapsulated solutes in membranes, synergistic permeability of cargo drugs, and control of polymer crystallization and thermal properties. , Research on lipid–BCP hybrid membranes has been mainly conducted on lamellar systems in the form of vesicles dispersed in water, , monolayer suspended in water, or bilayers on solid supports, leaving a gap in our understanding of polymorphism of the lipid–BCP hybrid system. Nonetheless, lipid–BCP mixtures hold a huge potential in creating nonlamellar structures with increasingly complex structures and topologies given that each amphiphile has the ability to self-assemble into various nanostructures.…”
Section: Introductionmentioning
confidence: 99%